Bioaccumulation of heavy metals using aquatic plants in wastewater - Muliyadi Muliyadi; Purwanto Purwanto; Sri Sumiyati; Mussadun Mussadun (International Journal of Public Health Science (IJPHS), 2023)
Heavy metals are very harmful to the environment if present in excessive concentrations and will have an effect on humans if they interact directly. Knowing the findings of heavy metal bioaccumulation in aquatic plants when reducing pollutants in liquid waste is the main goal of this study. Various types of data were developed and analyzed to answer the specific goals set through the EBSCO, ProQuest, and Science Direct Search Engine, by looking at several parameters. Bioaccumulation data for aquatic plants in liquid waste were obtained from five articles that met the criteria. The findings showed that there are six types of plants that can be used as heavy metal bioaccumulators in wastewater, including Limnobium laevigatum, Salvinia auriculata, Lemna minor, Colocasia esculenta, T. latifolia, and T. palustris. Data was also obtained that most research was carried out using liquid waste originating from within the city with a research time ranging from 1-45 days. The heavy metals that were most commonly accumulated in these plants were Zn, Pb, Cr, Ni, Cu, Fe, Mn, and Cd. It can be concluded that bioaccumulation using aquatic plants is very reliable for various types of heavy metals that can be removed.